In‐hospital outcomes of transcatheter mitral valve repair in patients with and without end stage renal disease: A national propensity match study. Issue 2 (1st February 2021) - Khan, Muhammad Zia; Zahid, Salman; Khan, Muhammad U.; Kichloo, Asim; Jamal, Shakeel; Minhas, Abdul Mannan Khan; Munir, Muhammad Bilal; Balla, Sudarshan
Abstract: Objectives: To study trends of utilization, outcomes, and cost of care in patients undergoing undergoing transcatheter mitral valve repair (TMVr) with end‐stage renal disease (ESRD). Background: Renal disease has been known to be a predictor of poor outcome in patients with mitral valve disease. Outcome data for patients with ESRD undergoing TMVr remains limited. Therefore, our study aims to investigate trends of utilization, outcomes, and cost of care among patients with ESRD undergoing TMVr. Methods: We analyzed NIS data from January 2010 to December 2017 using the ICD‐9‐CM codes ICD‐10‐CM to identify patients who underwent TMVr. Baseline characteristics were compared using a Pearson 𝜒 2 test for categorical variables and independent samples t ‐test for continuous variables. Propensity matched analysis was done for adjusted analysis to compare outcomes between TMVr with and without ESRD. Markov chain Monte Carlo was used to account for missing values. Results: A total of 15, 260 patients (weighted sample) undergoing TMVr were identified between 2010 and 2017. Of these, 638 patients had ESRD compared to 14, 631 patients who did not have ESRD. Adjusted in‐hospital mortality was lower in non‐ESRD group (3.9 vs. <1.8%). Similarly, ESRD patients were more likely to have non‐home discharges (85.6 vs. 74.9%). ESRD patients also had a longer mean length of stay (7.9 vs. 13.5 days) and higher mean cost of stay ($306, 300 vs. $271, 503). Conclusion: ESRD is associated with higher mortality, complications, and resource utilization compared to non‐ESRD patients. It is important to include this data in shared decision‐making process and patient selection.